Ethnic entrepreneurs as agents of social change: Entrepreneurs, clans, social obligations and ethnic resources: the case of the Liangshan Yi in Sichuan - Thomas Heberer (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2004)
The following contribution is concerned with the entrepreneurship among on of the major ethnic minorities. It goes into the effects of Yi entrepreneurship on the social structures of Yi society, particularly the clans and their changing role and function. We adress central components of social resources of Yi entrepreneurs, for instance ethnic resources; moral obligations of entrepreneurs towards their clan or lineage; social impacts in the form of entrepreneurs becoming clan or lineage headmen; the growing significance of non-kinship relations, and processes of individualization. We conclude that entrepreneurs on the one side are still embedded in a framework of social morality and social and ethnic obligations, yet, on the other side, impact upon the change of the social structure of Yi society.
Keywords: 330; Entrepreneurship-Ansatz; Ethnische Gruppe; Sozialer Wandel; Sichuan